Magic tree house - Osborne, Mary Pope 1949- (Scholastic, 2003)
Jack and Annie travel in their magic treehouse to the year 1621, where they celebrate the first Thanksgiving with the Pilgrims and Wampanoag Indians in the New Plymouth Colony